Impelementasi Creating Shared Value dan Tingkat Kesejahteraan Peternak Sapi (Kasus: PT Great Giant Livestock di Desa Terbanggi besar, Lampung) - Fatimah, Khansa Nabilah; Siwi, Mahmudi (CANTING: Indonesian Community Development and Social Investment Journal, 2026)
This study analyzes the implementation of Creating Shared Value (CSV) and its relationship with the welfare of cattle farmers in Terbanggi Besar Village, Lampung. The research aims to identify CSV practices carried out by the company, measure farmers’ welfare levels, and analyze the relationship between the two. The study employed a quantitative approach supported by qualitative data through questionnaire and in-depth interviews with 30 partner farmers of PT Great Giant Livestock. Data were analyzed using cross-tabulation and Spearman’s Rank correlation test. The results show that CSV implementation has been in line with the concept, particularly in social innovation, new business models, and farmer participation, although external networking and entrepreneurship development remain limited. Farmers’ welfare is generally at a moderate level, with basic needs, education, housing, and income relatively fulfilled, while self-development aspects require further improvement. Correlation tests indicate a positive and significant relationship between CSV implementation and farmers’ welfare.